Stretch marks: a visible expression of connective’s involvement in autism spectrum disorders - Veronese, Sheila; Zoccante, Leonardo; Smania, Nicola; Sbarbati, Andrea (Frontiers in Psychiatry, 2023)
In autism spectrum disorders (ASDs) in the pediatric population, skin manifestations are generally attributable to the concomitance of allergic forms or to accidental, self-inflicted or abusive lesions. However, clinical evidence has highlighted the presence of an increasing number of abdominal stretch marks, probably caused by the increase in the number of obesity cases in the pediatric population, in general, and therefore also among autistic children. Stretch marks are often attributed to obesity, as they have an incidence of more than 50% in obese individuals. In the first part of this article we hypothesized that in addition to obesity there are other factors, such as a structural alteration on the skin in people with ASD, which can contribute/aggravate the phenomenon of stretch marks. Despite the high frequency with which stretch marks are found in children with ASD, this aspect has never been studied, the structure of the skin of children with ASD is not known. Furthermore, it is not known whether this structure is different from that of subjects without ASD. In the second part of the article, we hypothesized the mechanisms of the negative impact of simple abdominal stretch marks on the symptomatic picture of children with ASD. The presence of stretch marks, altered tactile perception, altered sensitivity to clothing fabrics can be a combination that influences development and determines negative consequences in the neurological picture of a child with ASD, as it is already known that the altered sensory perception in children with ASD contributes to the deterioration of social behavior. Furthermore, the presence of stretch marks may play a role in the postural and motor defects of children with ASD.